The Role of Familismo and Acculturation as Moderators of the Association Between Family Conflict and Substance Abuse on Latino Adult Males - Lopez-Tamayo, Roberto (Public Health (Fairfax), 2016)
The significant research gap on Latino adults who completed substance abuse treatment (SAT) impacts the provision of substance use prevention and treatment for this population. Given the need for culturally-appropriate SAT for Latinos, research that examines the role of cultural constructs and acculturation in relation to substance use behavior is warranted. The purpose of the present study is to test, based on the social control theory, a multiple moderation model using the PROCESS macro(1) to examine the moderating effect of Familismo on the association between history of family conflict and years of substance abuse on Latino males who completed SAT at different levels of acculturation (i.e., cultural orientation). Generational status (i.e., immigrant, U. S. born) and age are used as covariates. A total of 117 Latino male participants (M(age)= 37, 54% non-U.S. born with a mean length of stay of 19 years in the U.S.) who completed SAT from facilities located in the metropolitan area of Chicago completed self-report measures. Results from the multiple moderation analysis showa significant three-way interaction (family conflict × Familismo × acculturation), indicating that participants with Latino and bicultural orientation who endorse average to high levels of Familismo have fewer years of substance abuse compared to those with U.S. mainstream culture orientation and low Familismo. Findings illustrate the need for SAT that assesses for family conflict and integrates cultural aspects to reduce substance use behavior on Latino males.